Effect of the Metal Ion on the Anti T. Cruzi Activity and Mechanism of Action of 5-Nitrofuryl-Containing Thiosemicarbazone Metal Complexes - Guerrero-Nunez, J; Guerrero-Nunez, J (Wiley-VCH Verlag, 2014)
Chagas disease, caused by the protozoan parasite Trypanosoma cruzi, is a major health problem worldwide. In this work, we report the development of palladium and platinum metal complexes with 5-nitrofuryl-containing thiosemicarbazones (L) as bioactive ligands against T. cruzi and PTA (1,3,5-triaza-7-phosphaadamantane) as co-ligand. Eight new complexes of the formula [MCl(L)(PTA)] with M = Pd or Pt were synthesized and fully characterized. Most complexes showed similar activities against T. cruzi to those of the corresponding free thiosemicarbazone ligands. No significant differences between palladium and platinum complexes were observed. Metal compounds with the phenylthiosemicarbazone derivative were the most active ones (IC50 = 9.84?±?0.32 and 4.94?±?0.24 ?M for Pd2+ and Pt2+, respectively). The prepared complexes were not toxic on mammalian cells, showing selective indexes of more than 10-20. The ability of the complexes to be reduced in the parasite, which leads to toxic free radical species, was confirmed by the detection of OH· and nitroanion free radical species by ESR spectroscopy experiments. Gel electrophoresis and fluorescence experiments were consistent with an intercalating-like mode of DNA interaction for the complexes, but DNA interaction does not seem to be the main mechanism of anti T. cruzi action for these compounds. The results obtained show that complexation of the bioactive ligands with the selected metals is a valid strategy to obtain improved metal-based antiparasitic compounds. Copyright © 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.